2008
DOI: 10.1021/ma800949q
|View full text |Cite
|
Sign up to set email alerts
|

Specific Polymerization Mechanism Involving β-Scission of Mid-Chain Radical Yielding Oligomers in the Free-Radical Polymerization of Vinyl Ethers

Abstract: Butyl vinyl ether (BVE) was polymerized radically, and the resultant oligomeric poly(BVE)s were characterized mainly using MALDI-TOF-MS spectrometry. For a further structural identification, the poly(BVE) obtained in bulk was subsequently subjected to 1 H NMR measurement. Notably, an intensive peak assignable to -CH 2 C(dO)CH 2protons was observed unexpectedly although a peak assignable to -CHO proton as the terminal end-group generated via β-scission of growing polymer radical as a presumed chain-end forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 35 publications
1
26
1
Order By: Relevance
“…When Kumagai et al analyzed the produced oligomer by MALDI-TOF mass spectrometry, a peak series was identified that could be assigned to aldehyde end-group-functional PBVE. 122 This was in accordance with an addition fragmentation mechanism proposed by the authors, in which the expulsion of a butyl radical from the macroradical chain-end by bscission led to chain transfer and formation of the aldehyde endgroup. However, 1 H-NMR revealed the major species carried an intra-chain ketone instead of an aldehyde end-group.…”
Section: Branchingsupporting
confidence: 89%
“…When Kumagai et al analyzed the produced oligomer by MALDI-TOF mass spectrometry, a peak series was identified that could be assigned to aldehyde end-group-functional PBVE. 122 This was in accordance with an addition fragmentation mechanism proposed by the authors, in which the expulsion of a butyl radical from the macroradical chain-end by bscission led to chain transfer and formation of the aldehyde endgroup. However, 1 H-NMR revealed the major species carried an intra-chain ketone instead of an aldehyde end-group.…”
Section: Branchingsupporting
confidence: 89%
“…We first attempted the reaction with cyanomethyl substituted thiocarbonylthio compounds as chain transfer agents (CTAs) ( 1 a – 1 e , Figure 1 C, Figures S3‐S4 and Scheme S1). When CTAs from 1 a to 1 d were employed, polymers of low molecular weights ( M n , entries 1–4 in Table 1) were obtained at moderate to high conversions of M1 and M2 , which could be attributed to the oligomerization of VEs [18] . Although CTA 1 e has shown good control in the copolymerization of chlorotrifluoroethylene, [19] the employment of 1 e in the terpolymerization of FM1 resulted in poor VE conversion (entry 5).…”
Section: Resultsmentioning
confidence: 99%
“…The first employment of MS to prove the formation of macromonomers in acrylate systems comes from Grady and coworkers [85,97]. A recent MS study even shows that backbiting followed by b-scission seems to occur in RP of butyl vinyl ether, resulting in a carbonyl group being incorporated into the polymer backbone [98]. However, it is Barner-Kowollik and colleagues who have made far the greatest effort to study the consequences of b-scission in acrylate polymerization, using MS as their scalpel.…”
Section: Acrylate Systemsmentioning
confidence: 99%